Comparison of Thermodynamic Parameters and Corrosion Behaviors of Ti50Ni25Nb25 and Ti50Ni25Ta25 Shape Memory Alloys - Mohammed, S. S.; Balci, E.; Dagdelen, F.; Saydam, S. (Pleiades Publishing Ltd, 2022)
The effect of Ta and Nb (25 at %) on the thermal, mechanical, and corrosion behaviors of TiNi shape memory alloy has been investigated. Ta and Nb added TiNi shape memory alloy samples that were prepared using the arc melting technique. The composition and crystal structure of the TiNi alloys were characterized by SEM-EDX and XRD at room temperature. The Vickers microhardness technique was used for the microhardness of the samples. Differential Scanning Calorimetry (DSC) was used to determine the thermal behavior of the TiNi shape memory alloys. DSC results showed that after four different heating-cooling rate, both austenite transformation temperatures and hysteresis temperature were increased in both Ti50Ni25Nb25 and Ti50Ni25Ta25 alloys. The enthalpy and entropy change with elastic energy, and Gibbs free energy were calculated of Ti50Ni25Nb25 and Ti50Ni25Ta25 SMAs. The phases of the alloys were determined using the XRD pattern. SEM and OM results show that both alloys solidified in dendritic structure. Corrosion biocompatibility of the new alloy samples were studied by potentiodynamic corrosion technique in simulated body fluid. The corrosion test indicated that Nb has a more positive effect than Ta on the corrosion of the new SMA alloys, suggesting TiNiNb SMA to be better biocompatibility than TiNiTa SMA.
Keywords: NiTi shape memory alloy; TiNiNb; TiNiTa; corrosion resistance; microhardness